Manajemen dan Praktik Inklusif Pendidikan Tinggi bagi Penyandang Disabilitas: Studi Kasus di Dua Universitas Kalimantan Timur - Karmilasari, Vina; Apriliani, Fajar; Meiliyana, Meiliyana; Prihantika, Ita (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Inclusive access to higher education for persons with disabilities in Indonesia remains limited, as indicated by data from the National Disability Committee (2022) showing that only 2.8% of persons with disabilities continue to higher education. This study addresses the issue of weak inclusive governance in universities by examining two institutions in East Kalimantan-one public and one private-selected to compare managerial practices. Using a descriptive qualitative approach, data were collected through in-depth interviews with university leaders, lecturers, administrative staff, and students with disabilities, as well as through campus facility observations and policy document reviews. Thematic analysis was applied to identify key patterns. The findings reveal that inclusive practices remain partial and highly dependent on individual initiatives. For instance, Campus A has established a Disability Service Center, but its authority is limited, while Campus B lacks a formal structure and relies on ad-hoc solutions. Major challenges include the absence of standardized service guidelines, insufficient budget allocation, and weak monitoring systems. This study recommends the establishment of dedicated disability service units with clear authority, special budget allocation, and participatory monitoring mechanisms to ensure the sustainability of inclusive education in higher education institutions.